Surface darkening by abundant and diverse algae on an Antarctic ice cap - Thomson, Alex Innes; Gray, Andrew; Colesie, Claudia; Thomas, Naomi; Moulton, Hannah; Convey, Peter; Smith, Alison G.; Fretwell, Peter; Peck, Lloyd; Davey, Matthew P. (Nature Communications, 2025)
Algal blooms play important roles in physical and biological processes on glacial surfaces. Despite this, their occurrence and impacts within an Antarctic context remain understudied. Here, we present evidence of the large-scale presence, diversity and bioalbedo effects of algal blooms on Antarctic ice cap systems based on fieldwork conducted on Robert Island (South Shetland Islands, Antarctica). Algal blooms are observed covering up to 2.7 km2 (~20%) of the measured area of the Robert Island ice cap, with cell densities of up to 1.4 × 106 cells ml−1. Spectral characterisation reveal that these blooms increase melting of the ice cap surface, contributing up to 2.4% of total melt under the observed conditions. Blooms are composed of typical cryoflora taxa, dominated by co-occurring Chlorophyceae, Trebouxiophyceae, and Ancylonema. However, morphological variation and genetic diversity in Ancylonema highlight the influence of regional endemism and point to a large and under-characterised diversity in Antarctic cryoflora.
Keywords: Antarktis; Sør-Shetlandsøyene; biogeografi; biologi; kryosfæren; snøalger; økologi

Correlative and dynamic species distribution modelling for ecological predictions in the Antarctic: a cross-disciplinary concept - Gutt, Julian; Zurell, Damaris; Bracegridle, Thomas J; Cheung, William; Clark, Melody S; Convey, Peter; Danis, Bruno; David, Bruno; De Broyer, Claude; di Prisco, Guido; Griffiths, Huw; Laffont, Rémi; et al. (Polar Research, 2012)
Keywords: Antarktis; biodiversitet; biosfære; miljø; oseanografi; økologi; økosystemer

TerrANTALife 1.0 Biodiversity data checklist of known Antarctic terrestrial and freshwater life forms - Pertierra, Luis R.; Varliero, Gilda; Barbosa, Andrés; Biersma, Elisabeth M.; Convey, Peter; Chown, Steven L.; Cowan, Don; De Los Rios, Asunción; Escribano-Alvarez, Pablo; Fontaneto, Diego; Fraser, Ceridwen; Harris, Mathew; et al. (Biodiversity Data Journal, 2024)
Incomplete species inventories for Antarctica represent a key challenge for comprehensive ecological research and conservation in the region. Additionally, data required to understand population dynamics, rates of evolution, spatial ranges, functional traits, physiological tolerances and species interactions, all of which are fundamental to disentangle the different functional elements of Antarctic biodiversity, are mostly missing. However, much of the fauna, flora and microbiota in the emerged ice-free land of the continent have an uncertain presence and/or unresolved status, with entire biodiversity compendia of prokaryotic groups (e.g. bacteria) being missing. All the available biodiversity information requires consolidation, cross-validation, re-assessment and steady systematic inclusion in order to create a robust catalogue of biodiversity for the continent.We compiled, completed and revised eukaryotic species inventories present in terrestrial and freshwater ecosystems in Antarctica in a new living database: terrANTALife (version 1.0). The database includes the first integration in a compendium for many groups of eukaryotic microorganisms. We also introduce a first catalogue of amplicon sequence variants (ASVs) of prokaryotic biodiversity. Available compendia and literature to date were searched for Antarctic terrestrial and freshwater species, integrated, taxonomically harmonised and curated by experts to create comprehensive checklists of Antarctic organisms. The final inventories comprises 470 animal species (including vertebrates, free-living invertebrates and parasites), 306 plants (including all Viridiplantae: embryophytes and green algae), 997 fungal species and 434 protists (sensu lato). We also provide a first account for many groups of microorganisms, including non-lichenised fungi and multiple groups of eukaryotic unicellular species (Stramenophila, Alveolata and Rhizaria (SAR), Chromists and Amoeba), jointly referred to as "protists". In addition, we identify 1753 bacterial (obtained from 348117 ASVs) and 34 archaeal genera (from 1848 ASVs), as well as, at least, 14 virus families. We formulate a basic tree of life in Antarctica with the main lineages listed in the region and their “known-accepted-species” numbers.
Keywords: Antarktis; Sørishavet; biodiversitet; database; fauna; flora; mikroorganismer